Improved information hiding algorithm based on twice positioning in coding channel - Li-quan CHEN; Miao LU; Ai-qun HU; Xiao-yan SUN (Tongxin xuebao)
Based on analysis of existing information hiding algorithms and capacities in coding channel,the defects of those existing algorithms were pointed out,and an improved information hiding algorithm with capacity upper limit analysis and based on twice positioning was proposed.the proposed algorithm,the information hiding capacity upper limit is firstly computed before embedding,and used for comparison with the size of hiding secret data.Then,twice posi-tioning scheme and cyclic shift mechanism for choosing the embedding position were used in the proposed algorithm.Simulation results show that,compared with those existing algorithms,the proposed algorithm is able to avoid the risk of exposure of the secret channel caused by capacity exceeding of hiding data.It can not only improve the randomness of the embedding position,but also avoid the risk of overlap among different secret data.The hiding performances of the coding channel information hiding system are improved.